(3GdfXQjI GdfbOjI aj HMhK GdEJUGd (B/s - (3YhGWa, YHO GdQMeGfs ((3GdbGgQI, GdLRGFQ (B:s (3OGQ GdacQ GdYQHj (B;(3OGQ GdcJGH GdMOjK ,s, 2013)
(3gPG GdcJGH jMGhd GdcGJH GdGLGHI Ydi SDGd eMhQj jTZd GSGJPI GdGJUGd h GdUMGaI aj TeGd GdYGde h LfhHg h gh gd jecf dHMhK GdGJUGd h GdGYdGe Gf JJhUd Gdi GdeYQaI GdJj fMJGLgG dage h JZjjQ GdhGbY GdeLJeYj GdPj fYjTg Gf GdeJGHYI GdfbOjI dHMhK GdGJUGd cTaJ Yf YOe bOQJgG Ydi ehGLgI GdJMOj GdNGU HHfGA h JUeje UhQ PgfjI eMOOI ddehGba h GdGhVGY GdJj jWQMgG GdhGbYs
(3HHdjhZQGajG (B: (3U(B.212-219s
Keywords: (3GdGJUGds; (3GdEYdGes; (3Yde GdELJeGYs